PERLINDUNGAN HUKUM TERHADAP KONSUMEN TERKAIT SKINCARE (PERAWATAN WAJAH) OVERCLAIM DI INDONESIA - Zia, Halida; Agusta, Mario; Rahmawati, Deliana (RIO LAW JURNAL, 2025)
This research discusses legal protection for consumers who suffer losses due to overclaim practices in skincare products marketed online in Indonesia. Overclaim refers to promotional statements that provide excessive and misleading information regarding the benefits or ingredients of a product, which often do not correspond to factual or scientific evidence. This phenomenon has become increasingly prevalent along with the rise of e-commerce as a medium for selling beauty and skincare products and the intense competition among business actors in the industry. This study aims to examine the forms of legal protection available to consumers based on Law Number 8 of 1999 on Consumer Protection and related regulations, as well as to analyze the legal liability that may be imposed on business actors for overclaim practices. The research employs a normative juridical method with statutory and literature approaches. The results show that consumers have the right to accurate, clear, and honest information about the products they use, and business actors are obliged not to provide misleading information. Overclaim practices are proven to violate consumer protection principles and may be subject to legal sanctions in accordance with applicable laws. This study recommends strengthening the supervision of skincare product advertisements and enhancing consumer education to better understand their rights. Keywords: Consumer Protection, Skincare, Overclaim, E-Commerce, Legal Liability